A CORRELATIONAL STUDY BETWEEN STUDENTS’ SELFCONFIDENCE AND SPEAKING ABILITY AT NINTH GRADE STUDENTS OF SMP N 5 SURAKARTA IN 2022/2023 ACADEMIC YEAR - Aprilia Sekar Wulandari; Sri Handayani (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2022)
The purpose of this study was to know whether there is significant correlation between students’ self-confidence and speaking ability at ninth grade students of SMP N 5 Surakarta. In this research there are two variables , self-confidence as the independent variable, and speaking ability as the dependent variable. To gather the data, a questionnaire and a speaking ability test were used. The results of this study were determined through a quantitative method, and 252 ninth grade students from SMPN 5 Surakarta were involved in the population. From these students, 31 were selected as samples by the researcher. The researcher used a questionnaire with 30 statements to measure students' level of self-confidence. After analyzing the data, it was determined that their level of confidence was high and their level of speaking ability was good. It based on the result of Pearson's Correlation Method, the correlation value was 0.726. This means that the correlation level is high and there is a positive significant correlation between students’ self-confidence and speaking ability and the standard correlation range is between 0.60 and 0.799. This confirms that null hypothesis was rejected and alternative hypothesis was accepted. The data from ninth grade students at SMP N 5 Surakarta shows a significant correlation between students’ self-confidence and speaking ability. Key words: Speaking Ability, Correlational Study, Self-confidence,